Uji Aktivitas Antibakteri Ekstrak Etanol Propolis Lebah Trigona (Trigona Spp) terhadap Propionibacterium acnes Penyebab Jerawat - Isna Wardaniati; Denia Pratiwi (LPPM Universitas Abdurrab, 2017)
Bacterial resistence is one of the global problems both in developed countries and devoloping countries. The high cases of resistence to antibiotics require the discovery of new active substances such as antibiotics agents. Therefore, to prevent the occurence of bacterial resistance to antibacterials need to be developed research in the disovery of new drugs derived from nature one of them is propolis. Propolis is a substance produced by bees to protect the nest from variety of threats, either unfavorable environmental threats or other organism attacks. One of type of bee that produces propolis is Trigona bee ( Trigona spp). The type of chemical compounds contained in propolis are very complex, among others alkaloid, flavonoid, steroid, saponin and tannin. This research is laboratory experimental study that aim to determine the antibacterial activity of ethanol extract of Trigona spp bee propolis against Propionibacterium acnes by disc diffusion methode. The concentration of ethanol extract of propolis used was 10 %, 20%, 30 %, 40 % with positif positive using clindamycin. From the result of the research, the inhibitory power of of ethanol extract of Trigona spp bee propolis with concentration 10 %, 20 %, 30 % dan 40 % is 11,7 mm, 12,3 mm, 13,6 mm and 14, 3 mm.